Key predictors of church growth in Grater New York Conference - Miranda, Juan Carlos Niño de; Robert Jean-Marie, Charles (Anuario de Investigación UM, 2020)
The assumption of this study is that church growth principles can answer to the critical question of declining and plateaued of the churches in the North American Division of Seventh-day Adventist. In this Division, many churches are experiencing the stagnation stage.